Sociolinguistics Of Disabled Verses In The Qur’an (Reconstruction of Disabled Status in Islam) - Dwi Iskandar, Arip (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2024)
This research aims to examine the reconstruction of the status of people with disabilities (disabled) from an Islamic perspective by using a sociolinguistic approach to verses from the Qur’an relating to disabled people. The background to this research is the gap between Islam's progressive understanding of people with disabilities and the stigma and discrimination that people with disabilities still often experience in the Muslim community. The theoretical framework used is sociolinguistic theory. The research method used is qualitative content analysis of verses from the Qur’an that discuss disabilities. The research results show that the Qur’an gives high appreciation and respect to people with disabilities, but their understanding and treatment in Muslim society are often distorted by stigma and misconceptions. This research emphasizes the importance of reconstructing the understanding of Al-Qur'an verses related to disabilities so that they are in line with the principles of justice, equality, and inclusion taught by Islam. Keywords: Sociolinguistics; Disabled people in the Qur’an;  Status Reconstruction